The strategic value of digital transformation in the oil and gas industry - Laksa-Timinskis, Ainars (My University, 2019)
Digital maturity refers to the state in which an organization's digital achievements reach their limits. The following research focuses on the oil and gas industry as it is a digitally maturing industry, thus it is lagging behind the other industries in terms of digital maturity. This is due to the fact that firms in oil and gas industry are mainly concerned with the operations of their physical assets, while digitally mature firms are mainly focused on their digital assets. New ways of working and strategies are expected to allow firms to reach digital maturity faster compared to the traditional methodologies. Agile and DevOps are new ways of working that are widely spread across various industries. The following research focuses on the factors that are influencing digital maturity and how does digital maturity impacts firms performance. In order to evaluate the effect of agile and DevOps on digital maturity, the relationship between agile, DevOps and the influencing factors of digital maturity is analyzed. Additionally, this research raises the importance of a digital twin within the organization, especially within oil and gas industry.